KEWENANGAN PEMERINTAH DAERAH DALAM PERPANJANGAN HAK GUNA USAHA PERSEROAN TERBATAS PERKEBUNAN NUSANTARA V KEBUN AIR MOLEK DI KABUPATEN INDRAGIRI HULU - Anita Aisyah; Mexsasai Indra; Junaidi Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
This research is related to the authority of the local government in extending the Right to Cultivate the Limited Liability Company for the Nusantara V Plantation of Air Molek in Indragiri Hulu Regency. The local government also has the authority in the process. In the field it was found that the extension of the Cultivation Right that was carried out was not in accordance with the provisions of the legislation and there was a conflict in the community regarding the Land Cultivation Right of the Nusantara V Limited Liability Company. , the authority of the local government in extending the Rights to Cultivate Limited Liability Company Perkebunan Nusantara V Kebun Air Molek in the district of Indaragiri Hulu, second, the inhibiting factor in the extension of the Right to Cultivate the Limited Liability Company Perkebunan Nusantara V, the third, the procedure that should be applied in the extension of the Right to Cultivate the Right to Cultivate Limited Liability Company Perkebunan Nusantara V, Air Molek plantation in Indragiri Hulu district. This research is a sociological legal research, because the source of the data comes from field research using interview methods and literature review that relates to the problems studied, assisted by primary, secondary, and tertiary data. This study uses qualitative data analysis, described descriptively and summarized by the deductive method. From the results of the study, it was concluded that, firstly, the authority of the local government in extending the Land Use Rights for Limited Liability Company Perkebunan Nusantara V Kebun Air Molek in Indaragiri Hulu Regency is as a member of the land inspection committee B, determining prospective planters who are recipients of facilitation activities for the construction of new plantations by plantation companies, and giving a statement that the land is not in dispute, secondly, the inhibiting factor in the extension of the Limited Liability Company Perkebunan Nusantara V Kebun Air Molek is caused by the rejection by the community around the Cultivation Right and the incompatibility of the land use rights with the RTRW, third, the procedures that should be applied in the extension Right to Cultivate is to follow the applicable laws and regulations which regulate the procedure for extending the term of the Cultivation Right, the procedure for renewing the Cultivation Right, and provisions regarding the obligations of the holder of the Cultivation Right.Keywords: Authority, Local Government, Right to Cultivate